Two body density matrix of model nuclear matter - Mavromanatis, E.; Petraki Μ.; Clark, J. W. (HNPS Advances in Nuclear Physics, 2019)
A lowest-cluster-order variational calculation of the half-diagonal two-body density matrix ρ2(r1,r2,r’1) and the corresponding generalized momentum distribution n(p.Q) is performed for three representative models of nuclear matter containing central correlations. Dynamical correlations produce significant deviations from the results for a noninteracting Fermi gas. Calculations axe in progress that include higherorder cluster corrections as well as state-dependent correlations